Micro‐unmanned aerial vehicle‐based volcano observation system for debris flow evacuation warning. Issue 8 (2nd November 2018) - Nagatani, Keiji; Kiribayashi, Seiga; Yajima, Ryosuke; Hada, Yasushi; Izu, Tomoaki; Zeniya, Akira; Kanai, Hiromichi; Kanasaki, Hiroyuki; Minagawa, Jun; Moriyama, Yuji
Abstract: When a volcano erupts, molten rocks, ash, pyroclastic flow, and debris flow can cause disasters. Debris flow is responsible for enormous damage across large areas. This makes debris flow simulations a crucial means of determining whether to issue an evacuation warning for area residents. For safety purposes, restricted areas are designated around volcanos during eruptions, making it difficult to gather information (such as the amount and permeability of ash) required for precise debris flow simulations. An unmanned observation system, intended for use in such restricted areas, was developed to address this issue. The proposed system is based on a multirotor micro‐unmanned aerial vehicle (MUAV) that transports cameras, small devices to measure target environments, and a small robot to active volcanic areas. Several field tests were performed around active volcanoes for validation and system improvement. This study investigates five unmanned systems with field tests. The first one is an autonomous flight to collect three‐dimensional (3D) terrain information. The MUAV conducted the long flight at Mt. Unzen‐Fugen and evaluated the accuracy and calculation time of the developed 3D terrain model. The second one is a drop‐down‐type ash‐depth measurement scale. The scales were deployed at Mt. Unzen‐Fugen and confirmed its function. The third system is a soil‐sampling device to estimate permeability. The device is hung from the MUAV by a long tether and collects soil and gravels directly with two rollers, while the MUAV is hovering. Indoor experiments were conducted to evaluate the performance of the device, and field experiments were conducted to confirm the validation of the system in different volcanic environments. The fourth system is an unmanned surface flow measurement device to estimate permeability. The device carries a water balloon and breaks it when it lands on the ground. By observing water flow with mounted cameras, qualitative permeability can be estimated. Initial experiments were conducted at Mt. Unzen‐Fugen to confirm its function. The fifth system is a small ground vehicle with a rainfall sensor deployed by an MUAV. The MUAV carries a capturing net suspended from it and delivers and retrieves the ground vehicle, while it is hovering. Field experiments were conducted at Mt. Asama and Mt. Unzen‐Fugen to validate the function of the system. Data obtained by these systems can contribute to the improvement of debris flow simulations developed in the project. In this paper, the above systems and experiments to evaluate them are introduced, and debris flow simulation results are demonstrated to prove the effectiveness of the data obtained by the proposed systems. Each field‐test section includes a discussion of the lessons learned.